Digital transformation strategy adoption and business performance: a case study of selected companies in a developing economy - SIZANI, Thabo; MARWA, Nyankomo; AKINRINDE, Olawale Olufemi; ISAYOMI, Abiodun Samuel (Journal of Social Sciences)
Despite its numerous benefits to companies in modern era, digital transformation strategies are rarely adopted in developing countries. Consequently, this study demonstrates the benefits of digital transformation to performance of companies in developing economies and the reasons for non-adoption of digital transformation strategies in developing economies. The objective of the study was achieved by using case study analysis to analyse five companies from different industry in developed and developing economies. The findings of this study highlights the various ways digital transformation positively impacts a company’s performance by improving business processes, reducing costs, or growing the revenue of the company. Evidence from the study also points at the lack of a digital transformation strategy, shortage of skills, absence of leadership support and unavailability of budget as the main reasons for the low rate of digital transformation adoption in developing economies. The study, therefore, concludes that digital transformation has the potential to significantly improve company performance in developing economies. Companies in developing economies could increase their performances by leveraging digital technologies and overcoming common.